Answer: o well i dont really knwo
Step-by-step explanation:
Answer:
a) Here we have:
"In Family A, the youngest child is 7 years younger than the oldest, who is 18"
Let's define:
Y = age of the youngest child.
O = age of the oldest child.
Then we know that:
Y = O - 7
O = 18
Then we can replace the second equation into the first one:
Y = 18 - 7 = 11.
b) Here we have:
"In Family B, the middle child is 5 years older than the youngest child."
Let's define:
Y = age of the youngest child.
M = age of the middle child.
Here we have only one equation:
M = Y + 5.
Answer:
y=![\frac{-3x}{-2x+1}](https://tex.z-dn.net/?f=%5Cfrac%7B-3x%7D%7B-2x%2B1%7D)
Step-by-step explanation:
Answer:
64.
Step-by-step explanation:
By proportion to number of orange marbles = (40 / 5) * 8
= 320 / 5
= 64 .